Moralitas Kemanusiaan Berdasarkan Fakta Sosial Émile Durkheim Dan Ayat-Ayat Sosial M. Quraish Shihab - Aceng Fuad Hasim Ikbal (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
The focus of this study is more directed to the formation of morality humanity of two views that can be seen from reality social or the fact social Émile Durkheim passages of social M.Quraish Shihab who were about to give theological ideas in the field of social (social interaction) in life of the party, neighbours, social and state. Relevance in this study to education is very important, with look at the process education is part of process social interaction. In this research in terms of approach phenomenology with link fundamental principles, namely objective reality and the fact social be integrated with obyektifis tradisionalis and obyektifis modernis, prove that the role of the fact social good affect on value morality in individuals whose are at a of the community or social environment.The distinguish from second figures this is in terms of the essence, the nature and factor that influences the formation of morality. Émile durkheim views that value morality lead to the purpose of planting values compliance (obedience) and value respect (deference) based on good collectively. And the trait of the morality is evolusionistis (could still change) appropriate to the state of time and place the presence of morality itself and factor that influences of the morality based on to whom most powerful man at the stage of social and factors lessons morality from others. The same cannot be said the view contained in the The same cannot be said the view contained in the passages of social M. Quraish Shihab that the value of morality was more of a how every individual so they can played the role as the servants of Allah SWT were told to stay behind, who believe and guard against evil to him, whether it is the relationship between himself by eating his portion of the lord , as well as himself by eating his portion of individuals who are other. Was in the middle of the trait of moralitasnya absolute in nature (absolute / there is no) this would make their bargaining, dynamic (easily adjust) and all scripture is relevant (been received in any of a condition) .Of factors affect moralitasnya everything no matter what the to which he or she understand from a social environment, of nature and of the others especially on his or her parents as a teacher first in the reality of their. Relevance to education that is how to build climate social that lead to planting value morality